The Socio-Economic Implications of Mine Closure ⎯ A South African and Zimbabwean Scenario - Mugonda, M. (Mine Closure 2006: Proceedings of the First International Seminar on Mine Closure, 2006)
The late Julius Mwalimu Nyerere, first President of Tanzania, once said that “The purpose of development …is the creation of conditions… which enable man the individual, and man the species, to become his best.” In recent years, growing awareness that the conducive environment for business prosperity and economic growth is vulnerable to government activities/politics - government policies and regulations, has been matched by the realisation that mineral resources need to be managed in an integrated and systematic way, to ensure these resources contribute positively to current and future generations. Mining contributes significantly to economic activities, fixed investment, employment opportunities, infrastructure, secondary industries, gross capital formation and foreign exchange earnings in South Africa and Zimbabwe. The mining industry considers that the investment climate in terms of government policy, laws and regulations must be appropriate to the encouragement of private sector mining activity. It is believed that these factors have improved in South Africa and deteriorated in Zimbabwe. Political instability, economic meltdown and the lack of a positive track record on policy, together with external factors such as declining commodity prices, competition from other mining countries and global financial crises, have resulted in negative economic growth in Zimbabwe. The new political dispensation has improved the investment environment in South Africa (Granville, 2001). Mining-led settlement is often associated with tensions between corporate mining objectives, recipient community needs and state policies and goals for regional development. Mining-based settlement formation is therefore predicated on the continued availability of the mineral resource, the economic viability of its extraction and the vagaries of the mineral price fluctuations in the international minerals markets (Tanzier, 1980). As Wekwete (1994) observed: Urbanisation in Southern Africa is a product of colonial exploitation of primary raw materials …. Urban centres were created to service exploitation of primary products. In many cases they did not receive any more investment than that required for them to perform their services. In mining towns, for example, companies aimed to create centres whose existence was directly relevant to the mine, and hence when the minerals are depleted they become 'ghost' towns.